Diabetes and infection: assessing the association with glycaemic control in population-based studies. Issue 2 (February 2016) - Pearson-Stuttard, Jonathan; Blundell, Samkeliso; Harris, Tess; Cook, Derek G; Critchley, Julia
Summary: Diabetes is a leading cause of morbidity and mortality. The global burden of diabetes is rising because of increased obesity and population ageing. Although preventive and treatment measures are well documented for macrovascular and microvascular complications, little such guidance exists for infections in people with diabetes, despite evidence suggesting greater susceptibility to infections, and worse outcomes. In particular, few studies have characterised the relation between glycaemic control and infectious disease, which we discuss in this Review. Some large population-based observational studies have reported strong associations between higher HbA1c and infection risks for both type 1 and type 2 diabetes. However, studies are contradictory, underpowered, or do not control for confounders. Evidence suggests that better glycaemic control might reduce infection risk, but further longitudinal studies with more frequent measures of HbA1c are needed. Older people (aged 70 years or older) with diabetes are at increased risk of complications, including infectious diseases. There is more uncertainty about appropriate glycaemic control targets in this age group, and evidence suggests that glycaemic control is often neglected. Robust evidence from cohorts with sufficient numbers of older people would help to develop clinically relevant guidelines and targets to reduce mortality, morbidity, and antibiotic use, and to improve quality of life.